Endoscopic ultrasonography‐guided tissue acquisition for small solid pancreatic lesions: Does the size matter? - Yousuke Nakai; Tsuyoshi Hamada; Ryunosuke Hakuta; Kazunaga Ishigaki; Kei Saito; Tomotaka Saito; Naminatsu Takahara; Suguru Mizuno; Hirofumi Kogure; Kazuhiko Koike; Mitsuhiro Fujishiro (DEN Open, 2022)
Abstract Endoscopic ultrasonography‐guided tissue acquisition (EUS‐TA) is now an established technique to obtain the pathological diagnosis of solid pancreatic lesions (SPLs), but the diagnosis of small SPLS by EUS‐TA can still be difficult. We conducted a literature review and a meta‐analysis on the diagnostic yield of EUS‐TA according to the tumor size. In a meta‐analysis of 33 studies with 6883 cases, a pooled odds ratio (OR) of sensitivity was significantly higher in SPLs of >20 mm (OR 1.64, p = 0.02) and in SPLs of >10 mm (OR 3.05, p = 0.01), but not in SPLs of >30 mm (OR 1.18, p = 0.46). The meta‐analysis of accuracy also showed a similar trend: OR of 1.59 in SPLs of >20 mm (p < 0.01) and OR of 3.27 in SPLs of >10 mm (p < 0.01) and OR of 1.03 in SPLs of >30 mm (p = 0.87). The use of a 25‐gauge needle tended to improve sensitivity in small SPLs, though not statistically significant: OR of 1.25 and 2.82 in studies with and without a 25‐gauge needle (p = 0.08). The use of fine needle biopsy needles, slow pull method, and rapid on‐site evaluation did not significantly improve sensitivity in small SPLs. EUS‐TA for small SPLs, especially neuroendocrine neoplasms, is reported to have a high risk of adverse events. In summary, the diagnostic yield and safety of EUS‐TA for small (<20 mm) SPLs still needs improvement, and the best needle and technique for small SPLs should be further investigated.